Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The Level of Cybersecurity Awareness among Graduate Female Students  at King Saud UniversityMs. Ahad Abdulkader Altayeb ,Ms. Najla Turki Alwahbi ,Ms. Noura Ahmed Almoqren2. The reality of professional development for public school teachers in Lebanon and its obstacles from the perspective of a sample of principals: Teacher training in the Beirut Governorate as a modelMr. Ali Habib Mhanna3. Future scenarios for applying artificial intelligence techniques at the Training Department  at A Saudi government universityMs. Dalia Abdulaziz Al-Harbi ,Ms. Maryam Abdullah Al-Luhidan ,Ms. Salwa Abdo Mohammed ,Ms. Jamilah Faisal Al-Kathiri ,Prof. Fatima Abdulaziz Al-Tuwaijri4. The Effectiveness of Supervisory Methods on Teachers' Performance in Schools Affiliated with Al-Ulaya Education Office in RiyadhDr. Abdulaziz Nasser Al-Fadhil5. The Level of School Health Environment in the General Directorate of Education in Taif Governorate from the Perspective of Health Supervisors and Its Relationship with Some VariablesDr. Sulaiman Hamoud Al-Salmi,Mr. Mutaib Hashim Al-Hashaibri6. Psychometric Properties of the Assertive Behavior Scale for a Sample of Adolescents  in Makkah RegionMr. Muhammad Yahya Al-Hazzazi,Co-Prof. Saleh Yahya Al-Ghamdi7. Social networks and their relevance to children's mental health from the perspective of mothersMs. Ghaida Saud Al-Rehden
Keywords: Journal of Educational and Psychological Sciences